CAR modulates E-cadherin dynamics in the presence of adenovirus type 5. - Fawziyah Hussain; Penny E Morton; Marjolein Snippe; Janis Sullivan; Charlotte Farmer; Marisa L Martin-Fernandez; Maddy Parsons; George Santis (PLoS ONE)
Adenovirus (Ad) serotype 5 (Ad5) fiber competitively binds to the coxsackievirus and Ad receptor (CAR) to attach Ad5 to target cells and also disrupts cell junctions and facilitates virus escape at a late stage in Ad5 infection. Here we demonstrate that paracellular permeability in MCF7 and CAR overexpressing MCF7 (FLCARMCF7) cells is increased within minutes following the addition of Ad5 to cells. This is brought about, at least in part, by altering the molecular dynamics of E-cadherin, a key component of the cell-cell adhesion complex. We also demonstrate that the increase in E-cadherin mobility is constitutively altered by the presence of CAR at FLCARMCF7 cell junctions. As increased paracellular permeability was observed early after the addition of Ad5 to cells, we postulate that this may represent a mechanism by which Ad5 could disrupt cell junctions to facilitate further access to its cell receptors.